"(Dis)Embodied Voices" and (Dis)Appearing Dialects: Staging a Living Historiography of Early African American Women - Joyce, Valerie (Complutense Journal of English Studies, 2015)
The performance project (Dis)Embodied Voices documented and vivified long-forgotten Early American black women’s experiences by devising a living historiography from personal letters, memoirs, diaries, court records, poems, and newspapers. The nine original monologues became the play I Will Speak for Myself, which recovers sixteen women who lived between 1649 and 1865 from Vermont to New Orleans. By crafting performance through a rigorous investment in the historical evidence and a commitment to truthful depiction in every word and sound, the play enacts life as a free woman, as an indentured servant, and as a former slave. This paper explores the transformation of written texts into the (Dis)Embodied Voices performance script and, specifically, the development of each woman’s distinctive sound. In many ways, these women exemplify the origination of the American sound and each case posed unique issues of evidence, language construction, and dialect choices. Crafting credible identities required striking a delicate balance between scholarly rigor and artistic license, bringing historical research and performance together so that what begin as disembodied voices become distinctive characters that more accurately shape our understanding of the abolitionist movement, life after slavery, and the fight for women’s education and equality.